2016
DOI: 10.1177/0883073815624758
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Instant Messaging on School Performance in Adolescents

Abstract: Instant messaging may compromise sleep quality and school performance in adolescents. We aimed to determine associations between nighttime messaging and daytime sleepiness, self-reported sleep parameters, and/or school performance. Students from 3 high schools in New Jersey completed anonymous questionnaires assessing sleep duration, daytime sleepiness, messaging habits, and academic performance. Of the 2,352 students sampled, 1,537 responses were contrasted among grades, sexes, and messaging duration, both be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
0
24
0
6
Order By: Relevance
“…34 Indeed, Johnson and Roth reported a 2-year earlier onset of insomnia in adolescents with comorbid psychiatric disorders compared with those with insomnia alone. 21 Depression rate shifted from slightly higher in prepubescent boys to a twofold higher in girls coinciding with the onset of menarche.…”
Section: Ming Et Almentioning
confidence: 97%
See 2 more Smart Citations
“…34 Indeed, Johnson and Roth reported a 2-year earlier onset of insomnia in adolescents with comorbid psychiatric disorders compared with those with insomnia alone. 21 Depression rate shifted from slightly higher in prepubescent boys to a twofold higher in girls coinciding with the onset of menarche.…”
Section: Ming Et Almentioning
confidence: 97%
“…Finally, another study of New Jersey adolescents showed that females practiced more instant messaging than their male schoolmates during the night and that texting after lights out contributed to impaired sleep quantity and quality relative to males. 34 In addition to unaccounted-for variables, a descriptive questionnaire study has inherent limitations. The answers were self-reported by participants and subject to comprehension of the questions.…”
Section: Ming Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Most recent research on text messaging involves college or young adult samples (e.g., Holtzman et al, ; Hsieh & Tseng, ; Ishii, Rife, & Kagawa, ; McEwan & Horn, ; Ouelette & Michaud, ). Almost all studies rely on survey data (e.g., Abeele et al, ; Gallimberti et al, ; Grover et al, ; Ishii et al, ; Lenhart, ; Ling, ; McEwan & Horn, ; Nesi, Widman, Choukas‐Bradley, & Prinstein, ). However, important exceptions examine small samples of text messages of college students (Eshghinejad & Moini, ; Ouelette & Michaud, ) and young adults (Aledavood et al, ), as well as one laboratory study with college students (Holtzman et al, ).…”
Section: Empirical Investigations Of Adolescents’ Text Messagingmentioning
confidence: 99%
“…Some differences in sleep health have behavioral origins. For example, Grover et al (2016) found that female adolescents were more likely than males to engage in text messaging, both before and after lights out, and more likely to report daytime sleepiness. That said, there are also biological differences that are related to hormonal changes associated with puberty in general, and menstruation in particular (Johnson, Roth, Schultz, & Breslau, 2006), that persist into adulthood (Kische et al, 2016;Romans et al, 2015).…”
Section: Introductionmentioning
confidence: 99%